Repeat Sampling and Coliform Bacteria Detection Rates in New Jersey Domestic Wells. Issue 2 (3rd February 2015) - Atherholt, Thomas B.; Korn, Leo R.; Louis, Judith B.; Procopio, Nicholas A.
Abstract In compliance with the New Jersey Private Well Testing Act, 78, 546 wells (93, 787 samples, including samples from 13, 290 wells that were analyzed more than once) were analyzed for total coliform (TC) bacteria by one or more of 39 laboratories over a 10‐year period. Samples containing TC bacteria were further analyzed for the presence of either fecal coliform or E. coli (FC/EC) bacteria. The large population of wells sampled multiple times permitted a systematic study of the effect of repeat sampling on coliform bacteria detection rates. The detection rate increased with the number of times wells were sampled. In bedrock, TC bacteria were detected in 21% of the population of wells analyzed only once, 33% in the population sampled twice, and 43% in the population sampled three times. It was estimated that TC bacteria would be detected in 90% of all wells if each well was analyzed 10 times. For FC/EC bacteria, it was estimated that 21 and 68 samples, respectively, would be required to reach the 50% and 90% population detection rates. In the Coastal Plain (CP), many more samples would be required to achieve the same estimated population detection rates. The population detection rate estimates were also dependent on the type of method used, the pH of the well water, and the geologic formation in which wells were located. A single sample was not sufficient to detect coliform bacteria when present in well water.